Dimensi Sekularitas dan Spiritualitas: Pencarian Format Integrasi Ilmu dalam Membangun Kurikulum Pendidikan Islam - Nasril, Yeny; Salminawati, Salminawati; Usiono, Usiono (Hikmah, 2023)
Exploring the Dimensions of Secularity and Spirituality: A Series of Science Integration for Islamic Education Curriculum Development. The emergence of the terms secularity and spirituality arises because there is a stream of human understanding that seeks to separate religion from the social life of society, this concept is known as secular understanding. Conversely, there is also a human understanding that combines harmoniously between religion and social life. This understanding is certainly used as a basic material in the construction of the Islamic education curriculum. The purpose of this research is to know the concept of secularity and spirituality as well as the concept of integration of science for the construction of Islamic education curriculum. This research uses a qualitative method with a library research approach with inductive data analysis. The results of this study indicate that secularity and spirituality must have equality and harmony in the implementation and creation of the curriculum, so that it will be able to print students with understanding and religious content (spiritualization) and real life (secularity). This research can be used as a reference material in the development of Islamic education curriculum construction which currently must adapt to the times.